Interference Effect of Closely Spaced Foundation Footing on Settlement Variation - Damtew Melese; Dekebi Genemo; Yada Boru; Alemineh Desisa; Tigist Mezmur; Mulatu Tamru (Advances in Civil Engineering)
Industrialization and urbanization have run into situations where the construction of buildings is close to each other. This closeness arises due to the restricted available space in a practical construction manner. Such a situation was a reason for the cause of footing of the same and adjacent structures coming closer. This condition causes interference effects, soil-structure interaction, and the stress zone impact to behave differently other than the continuum soil media in the vicinity under the base of the foundation due to overlap stress distribution, which results in excessive foundation settlement. Therefore, the study aims to assess the interference effect of closely spaced footing on settlement variation. In this regard, comprehensive experimental soil properties were conducted using the American Society for Testing and Materials (ASTM) testing procedures to characterize soil behavior. The interference of two footings in the settlement is studied using 3D finite element analysis. The hardening soil was used to model the foundation soil medium using the Plaxis 3D program. Certain vital factors of two neighboring footings for differing maximum loads, distance, embedment ratio, soil layer, and groundwater level are discovered to impact overlapping footing influence. It is observed that the spacing between the footings increases, and the interference impact on the overlapping footings declines, reaching the isolated footing condition at spacing higher than five foundation footing dimensions and increasing when the spacing between the footings decreases.